Measurement of specific and nonspecific tissue uptake of antibodies in tumor by SPECT imaging and nonlinear compartmental modeling - Nicholas Cho; Jason Ho; Geoffrey Del Rosario; Shang-Fan Yu; Gregory Z. Ferl; C. Andrew Boswell (EJNMMI Research)
Abstract Background Understanding the mechanisms driving specific and nonspecific tissue uptake of antibodies can inform protein engineering strategies that maximize therapeutic efficacy in target tissues while minimizing off-target tissue toxicities. While in vitro cell assays are typically used to study these internalization mechanisms, there are few methods readily available to evaluate these pathways in vivo. Single photon emission computed tomography (SPECT) imaging with a non-residualizing radiohalogen probe can measure total levels of intact antibody, and a residualizing radiometal-chelate probe, in combination with a non-residualizing probe, can measure catabolized antibody associated with receptor-mediated and nonspecific internalization processes. Here, we describe a SPECT imaging study in human epidermal growth factor receptor 2 (HER2)-expressing tumor-bearing mice aimed at measuring whole body disposition kinetics of tumor-targeting trastuzumab (anti-HER2) and non-targeting (anti-gD) antibodies. Mice received these molecules labeled with either a non-residualizing prosthetic group ([125I]SIB) or with a residualizing radiometal-chelate (111In-DOTA). Results SPECT imaging data confirmed significant HER2-mediated tumor uptake and catabolism of anti-HER2, evidenced by the high 111In-DOTA-anti-HER2 signal over time relative to 111In-DOTA-anti-gD and the respective [125I]SIB-labeled molecules. [125I]SIB-anti-HER2 still showed noticeably higher tumor signal than [125I]SIB-anti-gD, demonstrating a meaningful pool of intact anti-HER2 in the interstitial tumor compartment. Spleen showed the greatest catabolism of both mAbs amongst all non-tumor tissues. Compartmental modeling of the SPECT data demonstrated that cell-associated anti-HER2 was primarily receptor-bound, with a peak receptor occupancy of 35% at 13 h post administration of a 10 mg/kg dose, with minimal free and pinocytosed mAb. Conclusion Here, we successfully developed an imaging and modeling approach to capture anti-HER2 antibody receptor binding as well as specific and nonspecific internalization over time in vivo. These data and analyses demonstrate the power of SPECT imaging using both non-residualizing and residualizing radioisotopes to better characterize the different biological states (free, bound, and catabolized) of antibodies within interstitial and intracellular compartments. Understanding these distinct antibody internalization mechanisms in tumor and non-tumor tissues enables more informed decisions on dose selection to optimize treatment of tumors with heterogeneous antigen expression while minimizing nonspecific toxicities.